Burnout Among Healthcare Workers in the COVID 19 Era: A Review of the Existing Literature - Leo, Carlo Giacomo; Sabina, Saverio; Tumolo, Maria Rosaria; Bodini, Antonella; Ponzini, Giuseppe; Sabato, Eugenio; Mincarone, Pierpaolo (Frontiers in Public Health, 2021)
In the current period of global public health crisis due to the COVID-19, healthcare workers are more exposed to physical and mental exhaustion – burnout – for the torment of difficult decisions, the pain of losing patients and colleagues, and the risk of infection, for themselves and their families. The very high number of cases and deaths, and the probable future “waves” raise awareness of these challenging working conditions and the need to address burnout by identifying possible solutions. Measures have been suggested to prevent or reduce burnout at individual level (physical activity, balanced diet, good sleep hygiene, family support, meaningful relationships, reflective practices and small group discussions), organizational level (blame-free environments for sharing experiences and advices, broad involvement in management decisions, multi-disciplinary psychosocial support teams, safe areas to withdraw quickly from stressful situations, adequate time planning, social support), and cultural level (involvement of healthcare workers in the development, implementation, testing, and evaluation of measures against burnout). Although some progress has been made in removing the barrier to psychological support to cope with work-related stress, a cultural change is still needed for the stigma associated with mental illness. The key recommendation is to address the challenges that the emergency poses and to aggregate health, well-being and behavioral science expertise through long term researches with rigorous planning and reporting to drive the necessary cultural change and the improvement of public health systems.